Designing gender-inclusive digital solutions for agricultural development - Müller, Anna; Berta Ortiz-Crespo; Steinke, Jonathan (2022)
Digital tools play an increasingly important role in agricultural research for development. Often, they fall short in fulfilling their promises for women or other marginalized groups. Adoption across these groups is often low. One key reason for this is a narrow and techno-centric perspective on digital tool design. Human Centered Design brings a change in perspective on digital innovations towards more inclusive design processes. Thisleaflet is a summary of the practical guide and toolkit for gender-inclusive digital design.